FAKTOR YANG MEMPENGARUHI PROFITABILITAS PERUSAHAAN NON KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - MEIRYANANDA PERMANASARI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2016)
The purpose of this research is to get an empirical evidence factors that influence profitability. Independent variables used in this research are fixed assets ratio, debt ratio, financial leverage ratio, sales to current assets ratio, sales to equity ratio, gross margin return on inventory ratio, expenses revenue ratio, net income, and current ratio. The population of this research are all non-financial companies except services sectors listed in Indonesia Stock Exchange (IDX) from the period of 2009 to 2013. Sample selection procedure carried out by using purposive sampling method with a total sample 66 non-financial companies except services sectors. Data are analyzed using multiple regression analysis. The empirical result indicates that fixed assets ratio, debt ratio, financial leverage ratio, sales to equity ratio, gross margin return on inventory ratio, expenses revenue ratio, and net income have influence toward profitability. Other independent variables such as sales to current assets ratio and current ratio do not have influence toward profitability.